Development of Spinner Educational Media with the Assistance Of Interactive Power Points in Basic Mathematics Learning - Nadiyah Azhar Firdausi; Kunti Dian Ayu Afiani; Ishmatun Naila (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
The development of this media aims to measure the feasibility of Spinner Education media assisted by Interactive Power Point as a student learning media in class IV material at Muhammadiyah 13 Elementary School. Education and Interactive Power Point, the level of practicality of Spinner education media and Interactive Power Point, and the effectiveness level of Spinner Education and Interactive Power Point media. This research uses the R&D or Research and Development method and refers to the ADDIE development model. The results of the analysis of material validation that has been carried out by researchers get a percentage of 89%, and media validation gets a percentage of 89%. The results of the practicality analysis of the media get a percentage of 90% of the teacher's response and get a percentage of 91% of the student's response. At the analysis stage of the effectiveness of the media to get a learning completeness presentation of 88%. So it can be concluded that the media is suitable for use in the learning process in elementary schools.